2003
DOI: 10.3354/meps250263
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of summer flounder stock enhancement potential using experimental ecology

Abstract: Stock enhancement is receiving increasing attention as a management tool to rebuild depleted fisheries. Unfortunately, proactive studies addressing the potential of stock enhancement to accomplish management goals prior to the implementation of enhancement efforts are uncommon. We outline an ecologically based, pilot protocol with which to address the potential of fisheries stock enhancement using hatchery-reared (HR) organisms, through trial releases coupled with laboratory and field experiments with juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Stock enhancement is one of the more expensive and least successful fishery management options available (Grimes 1998, Kellison et al 2003. To reduce the ecological uncertainties that often limit its success, a candidate release species' optimal habitat must be known together with this habitat's carrying capacity and how to minimize losses through predation (Rothlisberg 1998).…”
Section: Implications For Stock Enhancementmentioning
confidence: 99%
“…Stock enhancement is one of the more expensive and least successful fishery management options available (Grimes 1998, Kellison et al 2003. To reduce the ecological uncertainties that often limit its success, a candidate release species' optimal habitat must be known together with this habitat's carrying capacity and how to minimize losses through predation (Rothlisberg 1998).…”
Section: Implications For Stock Enhancementmentioning
confidence: 99%
“…In addition, Tatara et al (2011) found that while the stocking of hatcheryreared steelhead parr (Oncorhynchus mykiss) into experimental streams led to an increase in the composite (hatchery-reared and natural) population, the emigration of natural steelhead parr led to an overall decrease in the abundance of natural recruits. Evidence of displacement arising from overstocking is rare in marine systems, potentially due to the complex experimental framework required to detect population and community changes in manipulated ecosystems (some good examples can be found in Leber et al, 1995;Kellison et al, 2003;Brennan et al, 2008;Eggleston et al, 2008). It should be noted, though, that if fish survive to reproduce, density dependence may arise, such as increased mortality or displacement in subsequent generations.…”
Section: Constraining Trophic Impactmentioning
confidence: 94%
“…Multiple stock enhancement programs and pilot releases of hatchery-reared individuals appear to be successful (e.g., McEachron et al, 1994;Leber and Arce, 1996;Fushimi, 1998;Agnalt et al, 1999;Lenanton et al, 1999;Davis et al, 2005), whereas others suggest stock enhancement efforts are not or may not be logistically or economically advisable (Hilborn, 1998;Ottera 1999;Kellison et al, 2003;Kellison and Eggleston 2004). Because of the extensive effort necessary to estimate the success and possible ecological ramifications of stock enhancement, it is advisable to first address the likelihood of actually enhancing wild stocks using pilot studies, because failure at this stage would render future investigations of ecological and economic potential of stocking unnecessary (Kellison et al, 2003). If release scenarios determine that post-release survival of hatchery-reared organisms will achieve biological and economic goals (e.g., Kellison and Eggleston, 2004), then managers can focus on potential ecological impacts of release (e.g., Leber, 1995;McMichael et al, 1999).…”
Section: Introductionmentioning
confidence: 94%